2012
DOI: 10.5336/medsci.2011-23965
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Clinic Intervention Plus Psychodrama in Smoking Cessation and Effects on Cessation Outcome

Abstract: 630obacco use has been recognized as the leading preventable cause of death worldwide and health benefits of smoking cessation has been well documented.1,2 However, only a minority of tobacco users can achieve permanent abstinence in an initial quit attempt. Majority of the users persist in tobacco use for many years and they typically cycle through multiple periods of remission and relapse. Modern approaches Intensive Clinic Intervention Plus Psychodrama in Smoking Cessation and Effects on Cessation Outcome A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…Four studies were on adolescents, of which three were on adolescents with aggression problems in Turkey (reported as distinct studies [46–48]) and one on Latino immigrant adolescents in the US (the same study was reported in two separate articles [21, 22]). The remaining seven studies were on adult smokers in Turkey [49], men with opiate dependence in Iran [50], adults with burnout who work in public services in Finland [18], oncology nurses coping with burnout in Turkey [51], adults with Parkinson’s disease in Brazil [52], and adults with panic disorders in Bulgaria [30]. One study was on university students with low subjective well-being and high hopelessness in Turkey [53].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were on adolescents, of which three were on adolescents with aggression problems in Turkey (reported as distinct studies [46–48]) and one on Latino immigrant adolescents in the US (the same study was reported in two separate articles [21, 22]). The remaining seven studies were on adult smokers in Turkey [49], men with opiate dependence in Iran [50], adults with burnout who work in public services in Finland [18], oncology nurses coping with burnout in Turkey [51], adults with Parkinson’s disease in Brazil [52], and adults with panic disorders in Bulgaria [30]. One study was on university students with low subjective well-being and high hopelessness in Turkey [53].…”
Section: Resultsmentioning
confidence: 99%
“…In a study carried out in our country, it was indicated that the addition of psychodrama practice on the attempt of smoking cessation increased smoking cessation rates. (28).…”
Section: Discussionmentioning
confidence: 99%
“…Hastanin kendi çabasmi destekleme ve kisa ögütler davrani §sal egitimin temel unsurlaridir [27]. Sigara birakmada yogun klinik giri §im üzerine psikodrama pratiginin eklenmesinin sigara birakma oranlarmí anlamli ölcüde artirdigi da gösterilmi §tir [30]. Davrani §sal egitim ki §iye özel olabilecegi gibi grup terapisi §eklinde de yapilabilmektedir.…”
Section: Bulgularunclassified